The Effect of Leverage, Profitability, Accounting Profits and Good Corporate Governance to Price Stock on Company Manufacture Sub Sector Pharmacyi, Cosmetics and Necessity House Stairs in Exchange Effect Indonesia Period 2016-2019 - Jordan Jordan; Deffy Febbiola; Cindy Cindy; Evelyn Evelyn; Vanessa Vanessa; Herlina Novita (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
With the background of various different research results, we would like to review the effect of leverage, profitability, accounting profit and good corporate governance to price stock. Method research used is descriptive quantitative. Population company manufacture subsector pharmacy, cosmetics and necessity House stairs total 16 companies with technique purposive sampling obtained sample as much 11 companies. Technique though data used is regression multiple. Test results this in a manner Partial leverage and accounting profit take effect positive against the price stock while on profitability variable and GCG no effect on price stock. In concluison the fourth variable independent influential to price stock. From the results of the coefficient of determination using score that has been customized show a figure of 0, 501 which meaningful equal to 50,1% variation price stock affected by leverage, profitability, profit accounting and GCG the rest 49, 9% affected by other factors.